Audio–visual synchronization in reading while listening to texts: Effects on visual behavior and verbal learning. (January 2018) - Gerbier, Emilie; Bailly, Gérard; Bosse, Marie Line
Highlights: Audiovisually-synchronized vs. unassisted Reading While Listening were compared. Children's orthographic and semantic learning did not benefit from synchronization. Gaze data showed that synchronization triggered a capture onto the highlighted words. Preference for the synchronized condition was the highest for the poorest readers. Abstract: Reading while listening to texts (RWL) is a promising way to improve the learning benefits provided by a reading experience. In an exploratory study, we investigated the effect of synchronizing the highlighting of words (visual) with their auditory (speech) counterpart during a RWL task. Forty French children from 3rd to 5th grade read short stories in their native language while hearing the story spoken by a narrator. In the non-synchronized (S−) condition the text was written in black on a white background, whereas in the synchronized (S+) RWL, the text was written in grey and the words were dynamically written in black when they were aurally displayed, in a karaoke-like fashion. The children were then unexpectedly tested on their memory for the orthographic form and semantic category of pseudowords that were included in the stories. The effect of synchronizing was null in the orthographic task and negative in the semantic task. Children's preference was mainly for the S− condition, except for the poorest readers who tended to prefer the S+ condition. In addition, the children's eye movements were recorded during reading. Gaze was affected by synchronization, with fewer but longer fixations on words, and fewer regressive saccades in the S+ condition compared to the S− condition. Thus, the S+ condition presumably captured the children's attention toward the currently heard word, which forced the children to be strictly aligned with the oral modality.